Age- and disease-dependent increase of the mitophagy marker phospho-ubiquitin in normal aging and Lewy body disease. Issue 8 (3rd August 2018) - Hou, Xu; Fiesel, Fabienne C.; Truban, Dominika; Castanedes Casey, Monica; Lin, Wen-lang; Soto, Alexandra I.; Tacik, Pawel; Rousseau, Linda G.; Diehl, Nancy N.; Heckman, Michael G.; Lorenzo-Betancor, Oswaldo; Ferrer, Isidre; et al.
ABSTRACT: Although exact causes of Parkinson disease (PD) remain enigmatic, mitochondrial dysfunction is increasingly appreciated as a key determinant of dopaminergic neuron susceptibility in both familial and sporadic PD. Two genes associated with recessive, early-onset PD encode the ubiquitin (Ub) kinase PINK1 and the E3 Ub ligase PRKN/PARK2/Parkin, which together orchestrate a protective mitochondrial quality control (mitoQC) pathway. Upon stress, both enzymes cooperatively identify and decorate damaged mitochondria with phosphorylated poly-Ub (p-S65-Ub) chains. This specific label is subsequently recognized by autophagy receptors that further facilitate mitochondrial degradation in lysosomes (mitophagy). Here, we analyzed human post-mortem brain specimens and identified distinct pools of p-S65-Ub-positive structures that partially colocalized with markers of mitochondria, autophagy, lysosomes and/or granulovacuolar degeneration bodies. We further quantified levels and distribution of the 'mitophagy tag' in 2 large cohorts of brain samples from normal aging and Lewy body disease (LBD) cases using unbiased digital pathology. Somatic p-S65-Ub structures independently increased with age and disease in distinct brain regions and enhanced levels in LBD brain were age- and Braak tangle stage-dependent. Additionally, we observed significant correlations of p-S65-Ub with LBs and neurofibrillary tangle levels in disease. The degree of co-existing p-S65-Ub signals and pathological PD hallmarks increased in the pre-mature stage, but decreased in the late stage of LB or tangle aggregation. Altogether, our study provides further evidence for a potential pathogenic overlap among different forms of PD and suggests that p-S65-Ub can serve as a biomarker for mitochondrial damage in aging and disease. Abbreviations: BLBD: brainstem predominant Lewy body disease; CCCP: carbonyl cyanide m-chlorophenyl hydrazone; DLB: dementia with Lewy bodies; DLBD: diffuse neocortical Lewy body disease; EOPD: early-onset Parkinson disease; GVB: granulovacuolar degeneration body; LB: Lewy body; LBD: Lewy body disease; mitoQC: mitochondrial quality control; nbM: nucleus basalis of Meynert; PD: Parkinson disease; PDD: Parkinson disease with dementia; p-S65-Ub: PINK1-phosphorylated serine 65 ubiquitin; SN: substantia nigra; TLBD: transitional Lewy body disease; Ub: ubiquitin